The Effectiveness of Reciprocal Teaching Method Embedding Critical Thinking Towards MIA Second Graders’ Reading Comprehension of MAN 1 Kendari - Lestari, Andi Ayu (Universitas Halu Oleo, 2019)
This research is aimed to investigate the effectiveness of reciprocal teaching strategy embedding critical thinking for students’ reading comprehension at the second grade of MIA at MAN 1 Kendari. Quantitative and qualitative approaches were employed to investigate the effectiveness of the method, as well as students’ perception. The study was guided by two research questions: (a) does reciprocal teaching method embedding critical thinking (RTT+) affect MIA second graders’ reading comprehension; (b) how do students perceive RTT+? Ninety-seven students participated in the present study. The instruments of the study were reading comprehension test and questionnaires. Reading comprehension test was administered on two different occasions; before and after treatment, whereas questionnaires were administered prior to the end of the study. Paired sample t-test was employed to examine possible differences in students’ pre- and post- test scores. The results show significant improvement in students’ post-test scores. Implications of the study will be critically discussed in this paper. Key words: Reciprocal Teaching Method, Critical Thinking, RTT+, Reading Comprehension.